Peran Media Sosial dalam Mempengaruhi Kebijakan Pendidikan - Febrinal, Dian; Saputra, Septia Irnanda; Irawadi, Hermen; Rahmi, Sri; Nuraiman, Nuraiman (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to analyze the role of social media in influencing education policy in the digital era. This research uses a mixed approach, namely qualitative and quantitative, involving 300 respondents from various stakeholders, including students, parents, educators, and government officials. The data collection techniques that will be used in this research include surveys, interviews, and content analysis. The analysis used in this research employs SPSS for descriptive data and thematic analysis methods for interview results. The research results show that social media serves as an effective tool in disseminating information related to education policies, with 89% of respondents agreeing with this. Additionally, 70% of respondents stated that social media facilitates public participation in the education policy-making process. There is doubt about the extent to which input from social media is considered by policymakers, with 40% of respondents expressing skepticism about this. An analysis of the content of 300 posts related to education policy revealed that issues such as educational gaps, curriculum, and access to technology in online learning are top concerns for the community, with 75% of posts showing negative sentiment towards existing education policies. These findings show the importance of increasing digital literacy and creating a more inclusive mechanism so that people's voices on social media are more accommodated in policymaking